2000
DOI: 10.1046/j.1537-2995.2000.40020169.x
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear matrix protein is released from apoptotic white cells during cold (1‐6°C) storage of concentrated red cell units and might induce antibody response in multiply transfused patients

Abstract: NMP is released in the supernatant of red cell units. The results obtained from patients suggest that nuclear proteins released during apoptosis, once transfused, may induce an immune response in multiply transfused patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 46 publications
2
32
0
Order By: Relevance
“…2,10,23,27 However, various studies have suggested that apoptosis and loss of viability of residual white cells in leukodepleted blood that have been stored before being transfused may lead to the release of immunostimulatory white cell antigens and soluble biological mediators, resulting in sensitization of the recipients. 2,16,25,28 This may explain why we continue to see alloimmunization in our patients even after we started using leukodepleted units, as we only use the poststorage leukodepletion which is a suboptimal method. In our study, there was no statistically significant difference between splenectomized and nonsplenectomized patients as regards the alloimmunization rate (36.4% and 21.6%, respectively) (P value >0.05), although splenectomy was significantly associated with higher incidence of multiple alloantibodies/patient (P=0.025) and positive previous antibody screen (P=0.065).…”
Section: Discussionmentioning
confidence: 96%
“…2,10,23,27 However, various studies have suggested that apoptosis and loss of viability of residual white cells in leukodepleted blood that have been stored before being transfused may lead to the release of immunostimulatory white cell antigens and soluble biological mediators, resulting in sensitization of the recipients. 2,16,25,28 This may explain why we continue to see alloimmunization in our patients even after we started using leukodepleted units, as we only use the poststorage leukodepletion which is a suboptimal method. In our study, there was no statistically significant difference between splenectomized and nonsplenectomized patients as regards the alloimmunization rate (36.4% and 21.6%, respectively) (P value >0.05), although splenectomy was significantly associated with higher incidence of multiple alloantibodies/patient (P=0.025) and positive previous antibody screen (P=0.065).…”
Section: Discussionmentioning
confidence: 96%
“…Martelli 18 and Frabetti 19 and their colleagues describe, in this issue of TRANSFUSION , the occurrence of apoptosis in white cells, not in vivo, but in units of red cells and stored platelet concentrates, respectively. Martelli et al 18 describe the occurrence of apoptosis in neutrophils present in red cells as well as the presence of soluble nuclear matrix protein (NMP) released from white cells into the supernatant of red cell units during cold storage. These authors further make the case that when the NMP and the apoptotic white cells are transfused to multiply transfused recipients, they may cause autoantibody formation.…”
mentioning
confidence: 99%
“…Thus, although an immune response was documented, no evidence of a negative clinical impact was provided. Martelli et al 18 note in their discussion that those patients who received only white cell‐reduced red cells had no detectable autoantibodies. They postulate that, because there are some white cells left in such white cell‐reduced units, perhaps there is a threshold for the immune response against NMP.…”
mentioning
confidence: 99%
“…22 The release of these complexes is supported by the observation that specific nuclear matrix proteins are released from apoptotic cells in culture, 23 during viral infection, 24 or in cold stored blood units. 25 We also note that apoptosis in PBC shares unique characteristics 26 and that the major AMA epitopes are released intact from apoptotic cells. 27 The presentation of the SUMOylated autoantigens and the production of autoantibodies may follow the same mechanisms described for autoreactivity against other posttranslationally modified antigens.…”
Section: Discussionmentioning
confidence: 69%